Business Performance Analytics After Digital Workflow in IT Sector - Lobo, Alisha Edile; B., Anish (SFIMAR Research Review, 2022)
The era of IoT (Internet of Things) and computer technology in the contemporary times has played a major role in the present situation of COVID-19 pandemic where the world is facing the worst phase. This communicable disease has led to the economic break down of several nations. The sectors such as steel, automobile and allied manufacturing sectors have faced lot of losses during the pandemic. On the other hand, the IT and telecommunication sector has seen immense growth despite the pandemic attack. The workforce of these sectors has been â€œDigitally Smartâ€. The concept â€œwork from homeâ€ has contributed a lot to the IT sector. During the FY 2020-21, the employees of the IT sector were working from home connecting to the main frame through internet. In this paper, we would quantify the increase in business and efficiency of the IT employees after working from home and also, growth of business within the key verticals of the IT sector. We would use data analytics and estimate the Economic value addition for analysing work efficiency. The paper would also compare the performance of three consecutive financial years along with current FY 2020-2021. We would conduct quantitative research by taking three sample cases studies of three companies belonging to the IT sector. This research would estimate the business generated within the key verticals and overall revenue generated by the IT sector. The comparison would focus on the percentage increase in business and meet our objective of this paper. The paper would also explain about some of the latest work-efficient technologies used by the IT sector companies for efficient and effective development of software services and software infrastructural services.